Chaotic Motion of the Underactuation Planar Five-bar Mechanism with Variable Parameter - Ren Bichun; Xie Jin; He Shanghong (Jixie chuandong)
The motion state of a mechanism will be changed when its parameters undergo some changes.Focusing on the impact of the variations of the slider mass on the motions of an underactuation planar five-bar mechanism.By means of Simulink/SimMechanics and permutation entropy,the conditions for periodic（quasiperiodic）motion and chaotic motion are found by analysis the edge of chaos.Based on these conditions,the motions of the mechanism starting with periodic（quasiperiodic）motion and chaotic motion are studied under the circumstance that the slider mass is increased regularly.The results show that the motion of the mechanism will eventually be chaotic no matter what kinds of motion the mechanism begins with.